Epoxidation studies of 2-styrylchromones using Jacobsen’s catalyst and hydrogen peroxide and iodosylbenzene as oxidants - Santos, Clementina M.M. (2011)
The epoxidation of 2-styrylchromones 2a-h using Jacobsen’s Mn(III)[salen] complex 1 as catalyst is reported for the first time. Several studies were performed using both hydrogen peroxide and iodosylbenzene as oxidants, in order to obtain the α,β-epoxy-2-styrylchromones 3a-h regioselectively. Due to the low reactivity of the substrates and the highly unstable character of the formed epoxides, reactions should be interrupted at lower conversions to obtain acceptable yields, especially when hydrogen peroxide is used.